Living Things and Life as Government Practices in the School - Sanchez Reyes, Leslie Alexa (Universidad Pedagógica y Tecnológica de Colombia, 2017)
On research as a possibility of thinking influence and as an experience that transforms people’s life and practices, this text presents the following review of the field of study of living things and life at the school as exercise of power objects on the people and their ways of behaving. Consequently, it is possible to understand that the questions about the relations between living things and life constitute a field of appropriation of the living things in teaching practices, lifestyles, and conditions of existence derived from man-nature relations. Therefore, the question arises as to life, which constitutes a field of thought on aesthetics, politics, ethics, philosophy, and of course, pedagogy; thus allowing a question about oneself and about the possibility of governing life.